Modern doctors' view on the problem of diagnostics and treatment of asthenic syndrome in different regions of the Russian Federation - Yana D. Belousova; Anastasiya M. Tynterova; Vladimir V. Rafalskiy (Belgorod National Research University, 2024)
Introduction: The problem of asthenic disorders is determined by their high prevalence, the lack of diagnostic criteria and recommendations for therapy, and the absence of unified principles of coding in ICD-10. The aim of the study was to evaluate the current practice of neurologists and physicians of the Russian Federation (RF) in the diagnosis and pharmacotherapy of asthenic syndrome (AS). Materials and Methods: An anonymous author-developed questionnaire survey of physicians on the issues of diagnostics and treatment of asthenia was conducted on the Google forms platform. Results: Total 238 specialists from 23 regions of the RF, 62.5% of neurologists and 37.5% of physicians, took part in the survey. Women suffer from AS more often than men. AS is most frequently verified at the age of 40-60 (65.5%) and under 40 (39.6%). Doctors use the codes G90.8 - other disorders of the autonomic nervous system - and I67.8 - other specified cerebral vascular lesions. The main causes of AS are affective disorders in 67.2% of patients and infectious diseases in 70% of patients. Almost 67% of doctors use anxiety and depression assessment scale, and only 13% of respondents use MFI-20 scale. The choice of therapy depended on the psychopathologic syndrome in 73.9% of cases. Most doctors favored nootropic drugs, metabolic action drugs, and B vitamins. Conclusion: The current medical practice of diagnosing and treating AS was studied and informative data were obtained with regard to understanding the clinical-typological structure and nosological affiliation of AS. The results demonstrate the expediency of developing a unified algorithm for the management of patients with various manifestations of AS.